Importance of Rapid Diagnosis of Hemostatic Dysfunction in Patients with Injury and Acute Blood Loss - E. G. Ripp; M. N. Shpisman (Общая реаниматология)
Examining the hemostatic system in 436 patients with injury and acute blood loss by an instrumental low-frequency piezoelectric hemocoagulation technique permits one to assess the likelihood of thrombohemorrhagic complications and multiple organ dysfunction syndrome in early stages of disease. Key words: acute blood loss, hemorrhagic shock, APACHE, disseminated intravascular coagulation, multiple organ dysfunction syndrome.